Status, Wood Properties and Probable Uses of Lesser Used Species Recorded from Sitapahar Reserve Forest of Bangladesh - Chowdhury, Pinaki; Hossain, M. K.; Akhter Hossain, M.; Dutta, Shourav; Ray, Tusher Kumer (Indian Forester, 2017)
A study was conducted focusing status, wood properties and probable uses of lesser used species (LUS) recorded from Sitapahar Reserve Forest of Bangladesh in 2014. A total of 50 sample quadrats of 20Ã—20m in size were placed by applying systematic purposive sampling method. The study enumerated a total of 86 tree species having â‰¥ 4 cm DBH among which 32 species (about 37% of all species) were categorized as LUS belonging to 28 genera and 22 families. Family Anacardiaceae was represented by maximum number of LUS (4 species under 4 genera) followed by Moraceae and Combretaceae. Total tree density of LUS was 528 stem ha-1 where Holigarna caustica, Myristica linifolia, Pterospermum acerifolium and Trewia nudiflora showed higher tree density. Besides, total basal area of LUS was 10.47 m2 ha-1 where Tetrameles nudiflora, Swintonia floribunda, Holigarna caustica and Myristica linifolia exhibited higher basal area. About 60% of LUS was under 'Least Concern' conservation category. Wood of substantial number of LUS exhibited weak strength, straight grain, medium fine texture and non-durability. Considering their physical and mechanical properties, 11 LUSwere found suitable for endproducts which require wood of medium weight and moderate strength whereas, 9 species were suitable for end-products made from wood of high weight and high strength.